2018
DOI: 10.1097/ico.0000000000001530
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Corneal Thickness by Swept-Source Optical Coherence Tomography and Scheimpflug Camera in Virgin and Treated Fuchs Endothelial Dystrophy

Abstract: SS-OCT provides better reproducible and repeatable measurements of corneal thickness than those obtained with the Scheimpflug camera in patients with FECD or an endothelial transplant. Variations between examinations higher than the 95% LOA observed in our study should raise awareness of changes in the endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Regarding diagnostic devices, the slitlamp microscope alone was the most frequently used diagnostic device in 31 of 61 articles (51%), 6,13–42 whereas 11 articles (18%) used a slitlamp microscope in combination with other devices/methods, such as in vivo confocal microscope (IVCM), 43–47 specular microscope, 48–51 pachymetry, 49,50 AS-OCT, 46 interview, 52 and histological diagnosis (Table 2). 53 Overall, slitlamp examination was used in 45 of 61 articles (74%).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding diagnostic devices, the slitlamp microscope alone was the most frequently used diagnostic device in 31 of 61 articles (51%), 6,13–42 whereas 11 articles (18%) used a slitlamp microscope in combination with other devices/methods, such as in vivo confocal microscope (IVCM), 43–47 specular microscope, 48–51 pachymetry, 49,50 AS-OCT, 46 interview, 52 and histological diagnosis (Table 2). 53 Overall, slitlamp examination was used in 45 of 61 articles (74%).…”
Section: Resultsmentioning
confidence: 99%
“…Arnalich-Montiel et al demonstrated that AS-OCT is superior to the Scheimpflug imaging system in visualizing deep corneal tissue, even in eyes with corneal opacity. 14 As an objective grading in FECD, anterior corneal backscatter of Scheimpflug images is reportedly higher in FECD. [15][16][17][18][19] Alnawaiseh et al 18 evaluated corneal light backscatter (densitometry) of the posterior cornea (60 mm from DM including the posterior stroma) and found that corneal light backscatter was greater in FECD than in normal controls and decreased after DSAEK or DMEK.…”
Section: Discussionmentioning
confidence: 97%
“…We opted to use anterior segment OCT rather than Scheimpflug imaging, as the former is considered to deliver more accurate and reliable measurements of corneal volume (Arnalich‐Montiel et al. ). Previous reports indicate that corneal thinning results from long‐standing, severe inflammation (Meisler et al.…”
Section: Discussionmentioning
confidence: 99%